A new Marasmius species (Agaricales, Marasmiaceae) with sessile basidiomata growing on wood, from Yunnan, China - Zhang, Qiu-Yue; Si, Jing; Li, Hai-Jiao (Phytotaxa, 2023)
Marasmius yunnanensis, a new species belonging to Marasmius section Marasmius, was found in Yunnan Province, southwestern China. It is characterized by its minute basidiomata, a conchoidal, reniform to semicircular pileus, a short to inconspicuous stipe, complete or incomplete collarium, Rotalis-type and smooth cheilocystidia and pileipellis cells, and ellipsoid basidiospores measuring 8–10 × 5–6.2 μm. It is described, illustrated, and compared with similar taxa according to morphological and molecular data.